Navigating the Uncharted: A Phenomenological exploration of Male Students Dating Gay Partners in the Municipality of Pinukpuk, Kalinga - Dela Peña, Manuel Jr (International Journal of Sustainability and Advanced Integrated Research, 2026)
This phenomenological study explored the lived experiences of male students in the Municipality of Pinukpuk, Kalinga who are involved in romantic relationships with gay partners. Anchored in Identity Negotiation Theory, Hegemonic Masculinity, and Social Identity Theory, the study examined how participants negotiate identity, masculinity, emotional vulnerability, and social perceptions within a culturally conservative environment. A qualitative phenomenological research design was employed using purposive sampling to select 10 male students from high school and college levels. Data were gathered through semi-structured written interviews conducted via Google Forms and analyzed using thematic analysis to identify recurring themes and patterns in the participants’ narratives. The findings revealed that participants experienced discrimination, teasing, and social pressure rooted in heteronormative expectations and the indigenous concept of bain (shame). To manage these challenges, students commonly adopted the strategy of “dedma” or ignoring criticism to maintain identity security and academic focus. The study further found that dating gay partners did not diminish the participants’ sense of masculinity; instead, they reconstructed masculinity through self-acceptance, emotional openness, and authenticity. Relationships were also described as sources of emotional intimacy, practical support, and personal growth, contributing to increased maturity, responsibility, improved hygiene, and stronger self-respect. The study concluded that these relationships serve as transformative spaces for resilience, identity reconstruction, and emotional development despite prevailing cultural pressures. Recommendations emphasized strengthening anti-discrimination policies, providing safe counseling spaces, promoting inclusive discussions on masculinity, and encouraging respectful community dialogue regarding non-traditional relationships. The study aligns with SDG 4 – Quality Education, SDG 5 – Gender Equality, and SDG 16 – Peace, Justice, and Strong Institutions by promoting inclusive educational environments, respect for diverse identities, and social understanding. Its sustainability contribution lies in fostering socio-cultural inclusion, emotional well-being, educational support systems, and community awareness within culturally sensitive contexts.
Keywords: Bain (Shame); Emotional Vulnerability; Identity Negotiation; Lived Experiences; Masculinity; Phenomenology; Personal Growth; Social Perceptions; Student Life; Thematic Analysis